THE INFLUENCE OF THE SCHOOL PRINCIPAL'S CHARISMATIC LEADERSHIP, ORGANIZATIONAL CULTURE, AND SELF-EFFICACY ON PERFORMANCE - HALIDA, Via (Journal of Education and Leadership in Education, 2024)
This research is aim to test empirically the influence of head master charismatic leadership organization culture and self efficacy against junior high school teacher performance in Sukmajaya District, Depok City. This research used quantitative approach with casual survey method and path analysis. The data analysis technique used descriptive statistic and inferential. The result of this research shows that: 1) There is positive effect and significant of head master’s charismatic leadership (X1) on teacher performance (X4) as big as ρ41 = 0,579 dan r14 = 0,920. 2) There is positive and significant effect of organization culture (X2) on teacher performance (X4) as big as ρ42 = 0,154 dan r24 = 0,457. 3) There is effect of head master’s charismatic leadership on self efficacy (X3) as bis as ρ31 = 0,742 dan r13 = 0,469. 4) There positive and significant effect of organization culture on self efficacy (X3) as big as ρ32 = 0,898 dan r23 = 0,920. 5) There’s positive and significant effect of head master’s charismatic leadership on (X1) on organization culture (X2) as big as ρ21 = 0,471 dan r12 = 0,471. 6) There’s positive and significant effect of self efficacy (X3) on teachers performance (X4) as big as ρ43 = 0,051 dan r34 = 0,472. Thus there is a positive and significant influence of the charismatic principal, organizational culture, self-efficacy on teacher performance.